Polymeric interlayer having improved acoustic properties

By using a polymer layer design with a specific composition of polyvinyl acetate (PVAc) resin and plasticizer, the problems of insufficient acoustic properties and compatibility of multilayer sandwich structures are solved, achieving the effect of improving acoustic performance and adhesion while maintaining optical and mechanical properties.

CN118055855BActive Publication Date: 2026-11-06SOLUTIA INC
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202280066994.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2022-01-11
Filing Date
2022-10-05
Publication Date
2026-11-06
Estimated Expiration
2042-10-05

AI Technical Summary

Technical Problem

Existing multilayer sandwich structures struggle to provide enhanced acoustic properties without compromising other optical or mechanical properties, and insufficient compatibility between polymer layers leads to inadequate adhesion, affecting the manufacturing and use of the sandwich structure.

Method used

A sandwich structure with improved acoustic properties is formed by using a polymer layer containing polyvinyl acetate (PVAc) resin and adjusting its glass transition temperature (Tg) and loss factor (tanδ) values. This structure includes a soft core layer and a hard skin layer. Furthermore, interlayer compatibility is improved by adjusting the use of plasticizers and the layer thickness design.

Benefits of technology

While maintaining other optical and mechanical properties of the interlayer, the acoustic performance is significantly improved, and the adhesion between polymer layers is enhanced, thus promoting the bonding and performance of the interlayer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118055855B_ABST
    Figure CN118055855B_ABST
Patent Text Reader

Abstract

A polymer interlayer having improved acoustic properties. The polymer interlayer includes a first polymer layer, a second polymer layer, and a third polymer layer. The first polymer layer is positioned between the second polymer layer and the third polymer layer. The first polymer layer is formed from a resin including polyvinyl acetate (PVAc). The first polymer layer has a T g greater than about 2.0.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polymer sandwich panels and multilayer panels comprising polymer sandwich panels. More specifically, this invention relates to the field of polymer sandwich panels comprising multiple polymer layers, their manufacture, and their uses. Background Technology

[0002] Multilayer panels are typically composed of two substrates (e.g., but not limited to glass, polyester, polyacrylate, or polycarbonate) and one or more polymer interlayers sandwiched between them. Laminated multilayer glass panels are commonly used in architectural windows and in motor vehicle and aircraft windows, as well as in photovoltaic solar panels. The first two applications are often referred to as laminated safety glass. The primary function of the interlayer in laminated safety glass is to absorb the energy generated by impacts or forces applied to the glass, allowing the glass layers to remain bonded together even under pressure and in the event of breakage, thus preventing the glass from shattering into sharp fragments. Furthermore, the interlayer can impart significantly higher sound insulation levels, reduce UV and / or IR light transmission, and enhance the aesthetic appeal of the window. For example, laminated glass panels with desired acoustic properties have been produced, resulting in quieter interior spaces.

[0003] Furthermore, laminated glass panels are already used in vehicles equipped with head-up display (“HUD”) systems (also known as head-up systems), which project images from the instrument cluster or other important information onto the windshield at eye level for the driver. This display allows the driver to visually access dashboard information while maintaining focus on the upcoming driving path. Typically, HUD systems in cars or airplanes use the inner surface of the windshield to partially reflect the projected image. However, secondary reflections occur on the outer surface of the windshield, forming a weak secondary image or “ghosting.” Because these two reflected images are offset in position, ghosting is frequently observed, creating an undesirable viewing experience for the driver. When an image is projected onto a windshield with a uniform thickness, interference ghosting or reflection ghosting occurs due to the difference in position of the projected image as it reflects off the inner and outer surfaces of the glass.

[0004] One way to resolve these ghosting or reflections is to orient the inner and outer glass panels at an angle to each other. This aligns the reflected image to a single point, creating a single image. Typically, this is achieved by employing a wedge-shaped or “conical” interlayer that displaces the outer sheet relative to the inner sheet, including at least one region of uneven thickness. Most conventional conical interlayers include a constant wedge angle across the entire HUD area, although some interlayers incorporating multiple wedge angles across the HUD area have recently been developed.

[0005] To achieve the desired properties and performance characteristics of glass panels (e.g., sound insulation, light transmission, HUD display, and / or enhanced aesthetic appeal), the use of multilayer or multi-layer sandwich structures has become common practice. As used herein, the terms "multilayer" and "multiple layers" refer to a sandwich structure with more than one layer, and the terms multilayer and multiple layers are used interchangeably. Multilayer sandwich structures typically contain at least one soft layer and at least one hard layer. As mentioned above, sandwich structures with a soft "core" layer sandwiched between two more rigid or harder "skin" layers have been designed to have sound insulation properties for glass panels. This construction is generally referred to herein as a "three-layer" sandwich structure. The soft "core" layer is considered the acoustic layer (because soft layers advantageously reduce sound transmission), while the hard "skin" layer is referred to as the conventional layer or non-acoustic layer.

[0006] Typically, the layers of a sandwich are produced by mixing a polymeric resin, such as poly(vinyl butyral), with one or more plasticizers, and then melting the mixture into a sheet using any suitable process or method known to those skilled in the art, including but not limited to extrusion, wherein the layers are bonded by methods such as co-extrusion and lamination. In a three-layer sandwich, the core layer may include more plasticizer than the skin layer, making the core layer softer than the relatively rigid skin layer. Other additional components may optionally be added for various other purposes, as described in more detail below. After the sandwich sheet is formed, it is typically collected and rolled for transport and storage, and subsequently used in multilayer glass panels as described below.

[0007] Multilayer glass panels are typically manufactured by combining with interlayers, and a simplified description of this process is provided below. First, a multilayer interlayer can be co-extruded using a multi-manifold co-extrusion apparatus. This apparatus operates by simultaneously extruding polymer melt from each manifold into the extrusion opening. The properties of the layer can be varied by adjusting the properties of the die lip at the extrusion opening (e.g., temperature and / or opening size). Once formed, an interlayer sheet is placed between two glass substrates, and any excess interlayer is trimmed from the edges to form the assembly. It is not uncommon to place multiple polymer interlayer sheets or a single polymer interlayer sheet with multiple layers (or a combination of both) between two glass substrates to form a multilayer glass panel with multiple polymer interlayers. Air is then removed from the assembly using suitable processes or methods known to those skilled in the art; for example, by rollers, vacuum bags, or another degassing device. Additionally, the interlayer is partially pressed onto the substrates using any method known to those skilled in the art. In this final step, to form the final single structure, this pre-bonding is made more durable by a high-temperature and high-pressure lamination process or any other method known to those skilled in the art, such as, but not limited to, high-pressure steam. The following is a simplified description of how multi-layer glass panels are typically produced in conjunction with interlayering.

[0008] In view of the above, there remains a need in the art to develop a multilayer sandwich that can provide enhanced acoustic characteristics without compromising other optical or mechanical properties of conventional multilayer sandwiches. More specifically, there is a need in the art to develop a multilayer sandwich having at least one soft core layer and one hard skin layer, which provides enhanced acoustic properties. Furthermore, there is a need for polymer layers in such a multilayer sandwich to exhibit suitable compatibility with each other in order to provide sufficient adhesive forces to promote bonding of the polymer layers during the fabrication and use of the sandwich. Attached Figure Description

[0009] Figure 1 This is a schematic diagram of a laminated glass panel, which includes a pair of glass plates opposite a polymer interlayer, wherein the polymer interlayer comprises three layers having a pair of skin layers opposite a core layer;

[0010] Figure 2 This is another schematic diagram of a laminated glass panel, comprising a pair of glass plates opposite a polymer interlayer, wherein the polymer interlayer has a wedge shape; and

[0011] Figure 3 The graph shows the tanδ values ​​of two different polymer sandwich sheets, one of which contains polyvinyl acetate (PVAc) with a glycerol-based plasticizer, and the other of which contains poly(vinyl butyral) (PVB).

[0012] Figure 4 This is a graph showing the tanδ values ​​of three different polymer sandwich sheets. Two of the polymer sandwich sheets contain polyvinyl acetate (PVAc) and ethylene glycol diester plasticizers, while the other polymer sandwich sheet contains poly(vinyl butyral) (PVB).

[0013] Figure 5 This is a schematic diagram of a two-dimensional sound transmission loss model used to simulate the sound transmission loss of laminated glass panels.

[0014] Figure 6 It includes Figure 4 A graph showing the simulated sound transmission loss of two glass panels in a polymer sandwich structure, where the sound transmission loss is calculated using... Figure 5 The transmission loss model was obtained;

[0015] Figure 7 The graph shows the tanδ values ​​of four different polymer sandwich sheets, three of which contain polyvinyl acetate (PVAc) with different amounts of ethylene glycol diester plasticizer, and the other polymer sandwich sheet contains poly(vinyl butyral) (PVB).

[0016] Figure 8 It includes Figure 7The graph shows the simulated sound transmission loss curves for the three glass panels of the polymer interlayer, where the sound transmission loss is calculated using... Figure 5 The transmission loss model was obtained;

[0017] Figure 9 It is a graph of the tanδ values ​​of three different polymer sandwich sheets, two of which contain hybrid polyvinyl acetate (PVAc) and the other contains poly(vinyl butyral) (PVB).

[0018] Figure 10 The graphs show the tanδ values ​​of two different three-layer polymer sandwiches, one of which has a core layer containing hybrid polyvinyl acetate (PVAc) and the other has a core layer containing poly(vinyl butyral) (PVB).

[0019] Figure 11 The graphs show the tanδ values ​​of two different three-layer polymer sandwiches, each of which has a core layer containing hybrid polyvinyl acetate (PVAc).

[0020] Figure 12 This is a graph showing the simulated sound transmission loss for three laminated glass panels. Each laminated glass panel has three polymer interlayers, two of which have a core layer containing hybrid polyvinyl acetate (PVAc), and the third polymer interlayer has a core layer containing poly(vinyl butyral) (PVB). The sound transmission loss is calculated using... Figure 5 The transmission loss model was obtained;

[0021] Figure 13 yes Figure 12 A graph showing the difference between simulated transmission losses;

[0022] Figure 14 This is another graph showing the simulated transmission loss for three laminated glass panels, each with three polymer interlayers. Two of these interlayers have a core layer containing hybrid polyvinyl acetate (PVAc), and the third interlayer has a core layer containing poly(vinyl butyral) (PVB). The transmission loss is calculated using... Figure 5 The transmission loss model was obtained;

[0023] Figure 15 yes Figure 14 A graph showing the difference between the transmission losses; and

[0024] Figure 16The graphs show the tanδ values ​​of two different polymer sandwiches. One polymer sandwich is a three-layer sandwich with a core layer containing poly(vinyl butyral) (PVB). The other polymer sandwich is a five-layer sandwich with a core layer containing polyvinyl acetate (PVAc), an adhesive layer containing hybrid polyvinyl acetate (PVAc), and a skin layer containing poly(vinyl butyral) (PVB). Summary of the Invention

[0025] One aspect of the present invention relates to a polymer sandwich layer having improved acoustic properties. The polymer sandwich layer includes a first polymer layer, a second polymer layer, and a third polymer layer. The first polymer layer is located between the second and third polymer layers. The first polymer layer is formed of a resin comprising polyvinyl acetate (PVAc). The first polymer layer has a Tc of less than about 20°C. g And a peak tanδ greater than approximately 2.0.

[0026] An additional aspect of the invention relates to a method of forming a polymer sandwich with improved acoustic properties. The method includes the step of extruding a first polymer melt to form a first polymer layer. An additional step includes extruding a second polymer melt to form a second polymer layer and a third polymer layer. During the extrusion step, the first polymer layer is located between the second and third polymer layers. The first polymer layer is formed from a resin comprising polyvinyl acetate (PVAc). The first polymer layer has a Tc of less than about 20°C. g And a peak tanδ greater than approximately 2.0.

[0027] An additional aspect of the invention relates to a polymer sandwich comprising a first polymer layer, a second polymer layer, and a third polymer layer. The first polymer layer is located between the second and third polymer layers. The first polymer layer is formed of a resin comprising hybrid polyvinyl acetate (PVAc). The first polymer layer has a Tc of less than about 20°C. g And a peak tanδ greater than about 1.5.

[0028] Another aspect of the invention relates to a polymer sandwich comprising a first polymer layer, a second polymer layer, and a third polymer layer. The first polymer layer is located between the second and third polymer layers. The first polymer layer is formed of a resin comprising polyvinyl acetate (PVAc). The polymer sandwich has a Tc of less than about 20°C. g And a peak tanδ greater than approximately 1.3. Detailed Implementation

[0029] Embodiments of the present invention relate to multilayer panels and methods of manufacturing multilayer panels. Typically, a multilayer panel consists of two glass or other suitable substrates, with one or more polymer interlayer sheets sandwiched between them. Multilayer panels are generally manufactured by placing at least one polymer interlayer sheet between two substrates to create an assembly. Figure 1 A multilayer panel 10 is shown, comprising a pair of glass sheets 12 sandwiched therebetween. The multilayer interlayer is configured as a three-layer interlayer having three separate polymer interlayer sheets, including a soft core layer 14 and two relatively rigid skin layers 16 positioned on either side of the core layer 14. However, in some additional embodiments of the invention, the multilayer interlayer may include more than three separate layers. For example, in some embodiments, the multilayer interlayer may include five layers, wherein an adhesive layer is located between the core layer 14 and each skin layer 16.

[0030] In some embodiments, the interlayer (e.g., core layer 14 and skin layer 16) will have a generally constant or uniform thickness with respect to the interlayer length. However, in alternative embodiments, such as Figure 2 As shown, the interlayer may have at least one region of non-uniform thickness. For example, the interlayer consisting of core layer 14 and skin layer 16 may be wedge-shaped, such that the thickness of the interlayer varies with respect to the length of the interlayer (e.g., linearly). In some such embodiments, the thickness of the interlayer may vary due to variations in the thickness of core layer 14 (i.e., skin layer 16 has a generally constant thickness). Alternatively, the thickness of the interlayer may vary due to variations in the thickness of skin layer 16 (i.e., core layer 14 has a generally constant thickness). In another alternative, the thickness of the interlayer may vary due to variations in the thickness of both core layer 14 and skin layer 16.

[0031] To facilitate a more comprehensive understanding of the mezzanine and multilayer panels disclosed herein, the meanings of certain terms as used herein will be defined. These definitions should not be construed as limiting the terms, as they are understood by those skilled in the art, but are merely intended to provide a better understanding of how certain terms are used herein.

[0032] As used herein, the terms “polymer sandwich sheet,” “sandwich,” “polymer layer,” and “polymer melt sheet” can refer to a single-layer sheet or a multilayer sandwich. As the name suggests, a “single-layer sheet” is a single polymer layer extruded as a single layer. On the other hand, a multilayer sandwich can include multiple layers, including individually extruded layers, co-extruded layers, or any combination of individually and co-extruded layers. Thus, a multilayer sandwich can include, for example: two or more single-layer sheets combined together (“multilayer sheets”); two or more layers co-extruded together (“co-extruded sheets”); two or more co-extruded sheets combined together; a combination of at least one single-layer sheet and at least one co-extruded sheet; and a combination of at least one multilayer sheet and at least one co-extruded sheet. In various embodiments of the invention, a multilayer sandwich includes at least two polymer layers (e.g., single-layer or co-extruded multilayers) arranged in direct contact with each other, wherein each layer comprises a polymer resin. As used herein, the term “resin” refers to a polymer component (e.g., PVAc or PVB) removed from the mixture, produced by acid catalysis and subsequent neutralization of a polymer precursor. Typically, plasticizers, such as those discussed more fully below, are added to the resin to produce a plasticized polymer. Additionally, the resin may have other components besides the polymer and plasticizer, including, for example, acetates, salts, and alcohols.

[0033] It should be understood that various thermoplastic interlayers can be used as polymeric resins for polymeric interlayers. Contemplated polymers include, but are not limited to, polyurethane, polyvinyl chloride, polyvinyl acetate (“PVAc”), poly(vinyl butyral”) (“PVB”), and combinations thereof. These polymers can be used alone or in combination with other polymers. Therefore, it should be understood that when ranges, values, and / or methods (e.g., plasticizer component percentage, thickness, and characterization of reinforcing additives) are given for a given polymeric interlayer in this application, these ranges, values, and / or methods can also be applied, where applicable, to other polymers and polymer blends disclosed herein, or can be modified to suit different materials as known to those skilled in the art. As used herein, the term “molecular weight” refers to weight-average molecular weight (Mw). The molecular weights of the PVAc or PVB resins disclosed herein can range, for example, from about 50,000 to about 600,000, from about 70,000 to about 450,000, or from about 100,000 to about 425,000 Daltons. In some preferred embodiments, the molecular weight of the PVAc resin can be in the range of about 100,000 to about 1,500,000 or about 200,000 to about 700,000 Daltons or about 500,000 Daltons.

[0034] When the resin compositions, layers, and interlayers described herein include a PVAc resin, the PVAc can be formed according to any suitable method and may contain a residual hydroxyl content and an optional aldehyde content (e.g., butyraldehyde) in addition to the desired percentage of acetate functional groups. For example, the PVAc resin of the present invention can be formed by free radical polymerization of vinyl acetate monomers to form a PVAc homopolymer in which the acetate content is substantially 100 wt%. Subsequent hydrolysis can yield a lower desired percentage of acetate with a residual hydroxyl content. If the free radical polymerization is carried out in the presence of ethylene or another copolymer, the amount of polyvinyl acetate residues in the polymer is at least 80 wt%, or at least 90 wt%, or at least 95 wt%, or at least 98 wt%. Therefore, the PVAc described herein may contain at least 80 wt%, or at least 90 wt%, or at least 95 wt%, or at least 98 wt% acetate.

[0035] Alternatively, the hybrid form of PVAc can be formed by acetalizing PVAc with an acid catalyst in the presence of one or more aldehydes, optionally with partial hydrolysis (resulting in a residual hydroxyl content). When acetalization is performed in the presence of an aldehyde (e.g., butyraldehyde), a residual aldehyde group is present in addition to the acetate and hydroxyl content. For example, the aldehyde content of PVAc may include one or more of acetaldehyde, propionaldehyde, isobutyraldehyde, or n-butyraldehyde. Therefore, the aldehyde content of PVAc can be 4wt%-45wt%, 4wt%-40wt%, 4wt%-35wt%, 4wt%-30wt%, 4wt%-25wt%, 4wt%-20wt%, 4wt%-15wt%, 4wt%-10wt%, 5wt%-45wt%, 5wt%-40wt%, 5wt%-35wt%, 5wt%-30wt%, 5wt%-25wt%, 5wt%-20wt%, 5wt%-15wt%, 5wt%-10wt%, 10wt%-45wt%, 10wt%-40wt%, 10wt%-35wt%, 10wt%-30wt%, 10wt%-25wt%, 10wt%-20wt%, 10wt%-20wt%, 10 wt%-15wt%, 15wt%-45wt%, 15wt%-40wt%, 15wt%-35wt%, 15wt%-30wt%, 15wt%-25wt%, 15wt%-20wt%, 20wt%-45wt%, 20wt%-40wt%, 20wt%-35wt%, 20wt%-30wt%, 20wt%-25wt%, 30wt%-45wt%, 30wt%-40wt%, 30wt%-35wt%, 40wt%-45wt%, and / or up to about 45wt%, or up to 40wt%, or up to 35wt%, or up to 30wt%, or up to 25wt%, or up to 20wt%, or up to 15wt%, or up to 10wt%. Furthermore, the residual hydroxyl content of the PVAc of the present invention may be, for example, about 4 wt% to about 30 wt%, or 4 wt% to about 25 wt%, or 4 wt% to 20 wt%, or 4 wt% to 15 wt%, or 4 wt% to 10 wt%, or about 5 wt% to about 30 wt%, or 5 wt% to about 25 wt%, or 5 wt% to 20 wt%, or 5 wt% to 15 wt%, or 5 wt% to 10 wt%, or 10 wt% to 25 wt%, or 10 wt% to 20 wt%, or 10 wt% to 15 wt%, or 15 wt% to 25 wt%, or 15 wt% to 20 wt%, and / or up to about 30 wt%, or up to 25 wt%, or up to 20 wt%, or up to 15 wt%, or up to 10 wt%, or up to 5 wt%.

[0036] The total percentage acetate content of the PVAc obtained according to the present invention may be at least about 40 wt%, at least 45 wt%, or at least about 50 wt%. Alternatively, unless otherwise specified, the percentage acetate content measured according to ASTM D-1396 may be at least about 55 wt%, or at least about 60 wt%, or at least about 65 wt%, or at least about 70 wt%, or at least about 75 wt%, at least 80 wt%, at least 85 wt%, at least 90 wt%, at least 95 wt%, at most 100 wt%, and / or 40 wt%-100 wt%, 40 wt%-90 wt%, 40 wt%-80 wt%, 40 wt%-70 wt%, 40 wt%-60 wt%, 40 wt%-50 wt%, 50 wt%-100 wt%, 50 wt%-90 wt%, 50 wt%-80 wt%. The percentages are 50wt%-70wt%, 50wt%-60wt%, 60wt%-100wt%, 60wt%-90wt%, 60wt%-80wt%, 60wt%-70wt%, 70wt%-100wt%, 70wt%-90wt%, 70wt%-80wt%, 80wt%-100wt%, 80wt%-90wt%, or 90wt%-100wt%. The total amount of any aldehyde residues in the PVAc resin can be collectively referred to as the acetal component. The balance of the PVAc resin is residual hydroxyl and residual acetate groups, which will be discussed in further detail below.

[0037] It should be understood that the PVAc resin of the embodiments of the present invention may include any combination of the above-described compositional values ​​(or ranges). For example, in some embodiments, PVAc may contain 40wt%-80wt% acetate, 5wt%-20wt% hydroxyl content, and 10wt%-45wt% aldehyde content. In some specific embodiments, PVAc may contain 50wt%-70wt% acetate, 10wt%-15wt% hydroxyl content, and 25wt%-35wt% aldehyde content. In some further specific embodiments, PVAc may contain about 60wt% acetate, about 10wt% hydroxyl content, and about 30wt% aldehyde content. In even further specific embodiments, PVAc may contain about 50wt% acetate, about 15wt% hydroxyl content, and about 35wt% aldehyde content. The term "hybrid" may be used herein in relation to a PVAc resin (or the resulting polymer layer) when the resin has at least 40 wt% acetate content in addition to non-nominal hydroxyl and aldehyde content (e.g., greater than about 4 wt% hydroxyl and / or aldehyde content). However, the general term "PVAc" as used herein may refer to a hybrid PVAc resin or a resin consisting essentially of polyvinyl acetate.

[0038] The resins forming the compositions, layers, and interlayers described herein can be prepared by known methods, such as those described below: "Solvent-Free Generation of Poly(Viny Acetals) Directly Poly(Vinyl Acetate)," in Polymer Engineering and Science, Volume 39, Issue 5, pages 862-871, by O'Neill, Mark L. (2004), the entire disclosure of which is incorporated herein by reference.

[0039] Although generally referred to herein as "poly(vinyl acetal)" or "poly(vinyl butyral)," the resins described herein may include any suitable aldehyde residues, including but not limited to isobutyral, as previously discussed. In some embodiments, one or more poly(vinyl acetal) resins may include at least one C1-C14 resin. 10 An aldehyde or a residue of at least one C4-C8 aldehyde. Suitable examples of C4-C8 aldehydes may include, but are not limited to, n-butyraldehyde, isobutyraldehyde, 2-methylpentanal, n-hexanal, 2-ethylhexanal, n-octanal, and combinations thereof.

[0040] In many embodiments, a plasticizer is added to a polymer resin to form a polymer layer or interlayer. Plasticizers are typically added to the polymer resin to increase the flexibility and durability of the resulting polymer interlayer. The plasticizer works by embedding itself between polymer chains, spacing them apart (increasing "free volume"), and thus significantly lowering the glass transition temperature (Tg) of the polymer resin. g This makes the material softer. In this respect, the amount of plasticizer in the interlayer can be adjusted to affect the glass transition temperature T. g Glass transition temperature T g This is the temperature at which the interlayer transitions from a glassy state to a rubbery state. Generally, a higher plasticizer loading results in a lower Tg. g In some embodiments, such as when the interlayer is an acoustic triple layer, the inner core layer (i.e., the soft layer) will have a glass transition temperature of less than about 20°C, while the outer skin layer (e.g., the hard layer) will have a glass transition temperature of greater than about 25°C. More broadly, the inner core layer (i.e., the soft layer) may be softer than the outer skin layer (e.g., the hard layer).

[0041] The anticipated plasticizers include, but are not limited to, glycerol-based plasticizers, ethylene glycol diester plasticizers, and / or combinations thereof. For example, glycerol-based plasticizers may include glyceryl tribose. Ethylene glycol diester plasticizers may include, for example, diesters having four or more repeating ethylene glycol units. For example, ethylene glycol diester plasticizers may include tetraethylene glycol di-(2-ethylhexanoate) (“4-GEH”), which comprises ethylene glycol diester molecules having four repeating ethylene glycol units. Furthermore, ethylene glycol diester plasticizers may include polyethylene glycol bis-(2-ethylhexanoate), which comprises ethylene glycol diester molecules having ten repeating ethylene glycol units.

[0042] In some embodiments, glycerol-based plasticizers and / or glycol diester plasticizers may comprise molecules having a specific oxygen-to-carbon ratio. Such a configuration can facilitate preferred solubility characteristics of the plasticizer. For example, in some embodiments, the oxygen-to-carbon ratio of the glycerol-based plasticizer and / or glycol diester plasticizer may be at least 0.32, at least 0.34, at least 0.36, at least 0.38, at least 0.40, at least 0.42, at least 0.44, at least 0.46, at least 0.48, or at least 0.50. In some embodiments, the oxygen-to-carbon ratio of the glycerol-based plasticizer and / or glycol diester plasticizer may be 0.32 to 0.50, 0.32 to 0.44, 0.32 to 0.40, 0.34 to 0.50, 0.34 to 0.44, 0.34 to 0.40, 0.36 to 0.50, 0.36 to 0.44, and / or 0.36 to 0.40.

[0043] Furthermore, in some embodiments, the glycerol-based plasticizer and / or ethylene glycol diester plasticizer may include preferred solubility properties. More specifically, the total solubility parameter δ of the material... tot It can be defined based on the material's Hansen solubility parameter. The total solubility parameter δ tot It can be derived from δ d δ p δ h The solubility contribution composition is represented by parameters indicating the solubility contributions from dispersion, polarity, and hydrogen bonding interactions, respectively. The δ0 of the material... tot It can be calculated using the following equation (1):

[0044] δ tot 2 =δ d 2 +δ p 2 +δ h 2 (1)

[0045] In some embodiments, the total solubility parameter δ of glycerol-based plasticizers and / or glycol diester plasticizers tot Polar solubility contribution δp The solubility parameters can be at least 3.7, at least 3.8, at least 3.9, at least 4.0, at least 4.4, at least 4.8, at least 5.0, at least 5.4, at least 5.8, at least 6.0, at least 6.4, at least 6.8, and / or at least 7.0. The unit for the solubility parameter is MPa. 1 / 2 Provided. In some embodiments, the total solubility parameter δ of the glycerol-based plasticizer and / or ethylene glycol diester plasticizer is provided. tot Polar solubility contribution δ p It can be 3.7 to 7.0, 3.8 to 6.0, and / or 3.8 to 6.0. In some embodiments, the total solubility parameter δ of the glycerol-based plasticizer and / or ethylene glycol diester plasticizer... tot Hydrogen bond solubility contribution δ h The total solubility parameter δ of the glycerol-based plasticizer and / or ethylene glycol diester plasticizer can be at least 4.6, at least 4.7, at least 4.8, at least 5.0, at least 5.2, at least 5.4, at least 5.6, at least 5.8, at least 6.0, at least 6.2, at least 6.4, at least 6.6, at least 6.8, at least 7.0, at least 7.2, at least 7.4, at least 7.6, at least 7.8, or at least 8.0. In some embodiments, the total solubility parameter δ of the glycerol-based plasticizer and / or ethylene glycol diester plasticizer is... tot Polar solubility contribution δ h It can be 4.6 to 8.0, 4.6 to 7.0, 4.8 to 8.0, 4.8 to 7.0, 5.4 to 8.0 and / or 5.4 to 7.0.

[0046] In addition, the polarity / hydrogen solubility parameter δ of the material (p,h) It can be made solely from δ p and δ h The solubility contribution composition, δ p and δ h These are parameters representing the solubility contributions from polar and hydrogen-bonded interactions, respectively. The δ of the material... (p,h) It can be calculated using the following equation (2):

[0047] δ (p,h) 2 =δ p 2 +δ h 2 (2)

[0048] In some embodiments, the polarity / hydrogen solubility parameter δ of the glycerol-based plasticizer and / or ethylene glycol diester plasticizer (p,h) The value can be at least 5.8, at least 6.0, at least 6.2, at least 6.5, at least 7.0, at least 7.5, at least 8.0, at least 8.5, and / or at least 9.0. In some embodiments, the polarity / hydrogen solubility parameter δ of the glycerol-based plasticizer and / or ethylene glycol diester plasticizer...(p,h) It can be 5.8 to 9.0, 6.0 to 9.0, and / or 7.0 to 9.0. In some embodiments, the polarity / hydrogen solubility parameter δ of the glycerol-based plasticizer and / or ethylene glycol diester plasticizer... (p,h) With the total solubility parameter δ tot The ratio (i.e., δ) (p,h) / δ tot The value can be at least 0.365, at least 0.375, at least 0.400, at least 0.420, at least 0.450, at least 0.500, at least 0.550, at least 0.600, at least 0.625, and / or at least 0.650. In some embodiments, the polarity / hydrogen solubility parameter δ of the glycerol-based plasticizer and / or ethylene glycol diester plasticizer... (p,h) With the total solubility parameter δ tot The ratio (i.e., δ) (p,h) / δ tot The values ​​can be 0.365 to 0.650, 0.375 to 0.650, 0.400 to 0.650 and / or 0.425 to 0.650.

[0049] Furthermore, in some embodiments, the molecular weight (Mw) of the ethylene glycol diester plasticizer can be at least 420 Daltons, at least 440 Daltons, at least 460 Daltons, at least 480 Daltons, at least 500 Daltons, at least 550 Daltons, at least 600 Daltons, at least 650 Daltons, at least 700 Daltons, at least 750 Daltons, and / or at least 800 Daltons. Additionally, the molecular weight (Mw) of the ethylene glycol diester plasticizer can be 420-800 Daltons, 420-750 Daltons, 440-800 Daltons, and / or 440-750 Daltons.

[0050] Typically, the plasticizer content of the polymer interlayer in this application will be measured in parts per hundred parts of resin (“phr”), expressed as a weight-to-weight ratio. For example, if 30 grams of plasticizer are added to 100 grams of polymer resin, the resulting plasticized polymer will have a plasticizer content of 30 phr. When the plasticizer content of a polymer layer is given in this application, the plasticizer content of a particular layer is determined with reference to the phr of the plasticizer in the melt used to prepare that particular layer. In some embodiments, the high-rigidity interlayer comprises layers with plasticizer contents of less than about 35 phr and less than about 30 phr.

[0051] According to some embodiments of the present invention, the total plasticizer content of one or more polymer layers described herein may be at least about 20 phr, at least about 25 phr, at least about 30 phr, at least about 35 phr, at least about 38 phr, at least about 40 phr, at least about 45 phr, at least about 50 phr, at least about 55 phr, at least about 60 phr, at least about 65 phr, at least about 67 phr, at least about 70 phr, or at least about 75 phr. In some embodiments, the polymer layer may further include one or more plasticizers not exceeding about 100 phr, not exceeding about 85 phr, not exceeding 80 phr, not exceeding about 75 phr, not exceeding about 70 phr, not exceeding about 65 phr, not exceeding about 60 phr, not exceeding about 55 phr, not exceeding about 50 phr, not exceeding about 45 phr, not exceeding about 40 phr, not exceeding about 38 phr, not exceeding about 35 phr, or not exceeding about 30 phr. In some embodiments, the total plasticizer content of at least one polymer layer may be in the range of about 20 phr to about 40 phr, about 20 phr to about 38 phr, or about 25 phr to about 35 phr. In other embodiments, the total plasticizer content of at least one polymer layer may be in the range of about 38 phr to about 90 phr, about 40 phr to about 85 phr, about 50 phr to 70 phr, about 55 phr to 65 phr, and / or about 60 phr or 62.5 phr.

[0052] When the interlayer comprises multiple layers, two or more polymer layers within the interlayer may have substantially the same plasticizer content and / or at least one polymer layer may have a different plasticizer content than one or more other polymer layers. When the interlayer comprises two or more polymer layers with different plasticizer contents, these two layers may be adjacent to each other. In some embodiments, the difference in plasticizer content between adjacent polymer layers may be at least about 1, at least about 2, at least about 5, at least about 7, at least about 10, at least about 20, at least about 30, at least about 35 phr and / or no more than about 80, no more than about 55, no more than about 50, or no more than about 45 phr, or in the range of about 1 to about 60 phr, about 10 to about 50 phr, or about 30 to 45 phr. When three or more layers are present in the interlayer, at least two polymer layers of the interlayer may have similar plasticizer contents falling within, for example, 10 phr, 5 phr, 2 phr, or 1 phr, while at least two polymer layers may have plasticizer contents that differ from each other according to the above ranges.

[0053] In addition to the specific plasticizers discussed above, the various polymeric layers (e.g., hard skin layers) of the interlayer discussed herein may include other types of plasticizers. For example, contemplated plasticizers include, but are not limited to, esters of polybasic acids, polyols, triethylene glycol di-(2-ethylbutyrate), triethylene glycol di-(2-ethylhexanoate) (referred to as "3-GEH"), triethylene glycol diheptanoate, tetraethylene glycol diheptanoate, dihexyl adipate, dioctyl adipate, cyclohexyl adipate, heptyl adipate and nonyl adipate mixtures, diisononyl adipate, heptyl nonyl adipate, dibutyl sebacate, and polymeric plasticizers such as oil-modified sebacate alkyd resins and mixtures of phosphate esters and adipates, and combinations thereof. 3-GEH is particularly preferred. Other examples of suitable plasticizers may include, but are not limited to, di(butoxyethyl) adipate and bis(2-(2-butoxyethoxy)ethyl) adipate, dioctyl sebacate, nonylphenyl tetraethylene glycol and mixtures thereof.

[0054] In some embodiments, one or more polymer layers or interlayers described herein may comprise blends of two or more plasticizers, including, for example, two or more plasticizers listed above. When a polymer layer contains two or more plasticizers, the difference between the total plasticizer content of the polymer layer and the total plasticizer content between adjacent polymer layers may fall within one or more of the ranges described above. When the interlayer is a multilayer interlayer, one or more polymer layers may comprise two or more plasticizers. In some embodiments, when the interlayer is a multilayer interlayer, at least one of the polymer layers comprising the plasticizer blend may have a glass transition temperature higher than that of a conventional plasticized polymer layer. In some cases, this can provide additional stiffness to the layer, which can be used as, for example, an outer “skin” layer in a multilayer interlayer.

[0055] In addition to plasticizers, adhesive control agents (“ACA”) are also considered to be incorporated into the polymer resin to form a polymer interlayer. When forming laminated panels, ACA typically acts to alter and / or improve the adhesion of the interlayer to the glass panel. Contemplated ACAs include, but are not limited to, magnesium carboxylate / magnesium salts. Additionally, contemplated ACAs may also include those disclosed in U.S. Patent 5,728,472, such as residual sodium acetate, potassium acetate, and / or magnesium bis(2-ethylbutyrate), which is incorporated herein by reference in its entirety.

[0056] Other additives may be introduced into the interlayer to enhance its performance in the final product and impart certain additional properties to the interlayer. These additives include, but are not limited to, dyes, pigments, stabilizers (e.g., UV stabilizers), antioxidants, anti-caking agents, flame retardants, IR absorbers or blockers (e.g., indium tin oxide, antimony tin oxide, lanthanum hexaboride (LaB6), and cesium tungsten oxide), processing aids, flow-enhancing additives, lubricants, impact modifiers, nucleating agents, heat stabilizers, UV absorbers, UV stabilizers, dispersants, surfactants, chelating agents, coupling agents, adhesives, primers, reinforcing additives, and fillers, as well as other additives known to those skilled in the art.

[0057] One parameter used to describe the polymer resin composition of the polymer interlayer of this application is the residual hydroxyl content (as vinyl hydroxyl content or poly(vinyl alcohol) (“PVOH”) content). The residual hydroxyl content refers to the amount of hydroxyl groups remaining as side groups on the polymer chain after processing. For example, PVB can be manufactured by hydrolyzing poly(vinyl acetate) to poly(vinyl alcohol), and then reacting the poly(vinyl alcohol) with butyraldehyde to form PVB. Similarly, PVAc can be formed by hydrolyzing PVAc to the desired acetate and hydroxyl content. During the hydrolysis of poly(vinyl acetate) to form PVB, not all acetate side groups are typically converted to hydroxyl groups. Furthermore, the reaction with butyraldehyde typically does not result in all hydroxyl groups being converted to acetal groups. Therefore, in any finished PVAc or PVB, there will typically be residual acetate groups (as vinyl acetate groups) and residual hydroxyl groups (as vinyl hydroxyl groups) as side groups on the polymer chain. Generally, the residual hydroxyl content of the polymer can be adjusted by controlling the reaction time, reactant concentration, and other variables in the polymer manufacturing process. When used as a parameter in this article, the residual hydroxyl content is measured as a weight percentage according to ASTM D-1396.

[0058] When combined with at least one plasticizer, poly(vinyl acetal) resins with higher or lower residual hydroxyl content and / or residual acetate content may ultimately include varying amounts of plasticizer. As a result, layers or domains formed from a first poly(vinyl acetal) resin and a second poly(vinyl acetal) resin with different compositions may also exhibit different properties within a single polymer layer or interlayer. It is noteworthy that, for a given type of plasticizer, the compatibility of the plasticizer in the polymer is primarily determined by the polymer's hydroxyl content. Polymers with a higher residual hydroxyl content are generally associated with reduced plasticizer compatibility or capacity. Conversely, polymers with a lower residual hydroxyl content generally result in increased plasticizer compatibility or capacity. Consequently, poly(vinyl acetal) resins with higher residual hydroxyl content tend to be less plasticized and exhibit higher stiffness than similar resins with lower residual hydroxyl content. Conversely, when plasticized with a given plasticizer, poly(vinyl acetal) resins with lower residual hydroxyl content may tend to incorporate higher amounts of plasticizer, which can result in a softer polymer layer that exhibits a lower glass transition temperature than similar resins with higher residual hydroxyl content. These tendencies can be reversed depending on the specific resin and plasticizer.

[0059] When two poly(vinyl acetal) resins with different residual hydroxyl content levels are blended with a plasticizer, the plasticizer can be distributed between polymer layers or domains, allowing more plasticizer to be present in layers or domains with lower residual hydroxyl content and less plasticizer to be present in layers or domains with higher residual hydroxyl content. Ultimately, an equilibrium is reached between the two resins. This correlation between the residual hydroxyl content of the polymer and the plasticizer compatibility / capacity can typically be manipulated and utilized to allow for the addition of appropriate amounts of plasticizer to the polymer resins and to stably maintain the difference in plasticizer content within the multilayer interlayer. This correlation also helps to stably maintain the difference in plasticizer content between two or more resins as the plasticizer migrates between them.

[0060] Because plasticizers migrate within the interlayer, the glass transition temperatures of one or more polymer layers may differ when measured individually or as part of a multilayer interlayer. In some embodiments, the interlayer may include at least one polymer layer whose glass transition temperature outside the interlayer is at least about 33°C, at least about 34°C, at least about 35°C, at least about 36°C, at least about 37°C, at least about 38°C, at least about 39°C, at least about 40°C, at least about 41°C, at least about 42°C, at least about 43°C, at least about 44°C, at least about 45°C, or at least about 46°C. In some embodiments, the glass transition temperature of the same layer within the polymer layer may be at least about 34°C, at least about 35°C, at least about 36°C, at least about 37°C, at least about 38°C, at least about 39°C, at least about 40°C, at least about 41°C, at least about 42°C, at least about 43°C, at least about 44°C, at least about 45°C, at least about 46°C, or at least about 47°C.

[0061] In the same or other embodiments, the glass transition temperature of at least one other polymer layer of the multilayer interlayer can be less than 30°C, and the glass transition temperature measured, for example when the interlayer is not part of the interlayer, can be no more than about 25°C, no more than about 20°C, no more than about 15°C, no more than about 10°C, no more than about 9°C, no more than about 8°C, no more than about 7°C, no more than about 6°C, no more than about 5°C, no more than about 4°C, no more than about 3°C, no more than about 2°C, no more than about 1°C, no more than about 0°C, no more than about -1°C, no more than about -2°C, or no more than about -5°C. When measured outside the interlayer, the glass transition temperature of the same polymer layer can be no more than about 25°C, no more than about 20°C, no more than about 15°C, no more than about 10°C, no more than about 9°C, no more than about 8°C, no more than about 7°C, no more than about 6°C, no more than about 5°C, no more than about 4°C, no more than about 3°C, no more than about 2°C, no more than about 1°C, or no more than about 0°C.

[0062] According to some embodiments, the difference between the glass transition temperatures of two polymer layers (typically adjacent polymer layers within a sandwich structure) can be at least about 5°C, at least about 10°C, at least about 15°C, at least about 20°C, at least about 25°C, at least about 30°C, at least about 35°C, at least about 35°C, or at least about 35°C. In other embodiments, the glass transition temperatures of two or more polymer layers can be within about 5°C, about 3°C, about 2°C, or about 1°C of each other. Typically, the layer with the lower glass transition temperature has a lower stiffness than one or more layers with higher glass transition temperatures in the sandwich structure and can be located between the polymer layers with higher glass transition temperatures in the final sandwich structure.

[0063] For example, in some embodiments of this application, the increased acoustic attenuation properties of the soft layer are combined with the mechanical strength of the hard / rigid layers to create a multilayer sandwich. In these embodiments, the intermediate soft layer is sandwiched between two hard / rigid outer layers. This (hard) / / (soft) / / (hard) configuration produces a multilayer sandwich that is easy to handle and can be used in conventional lamination methods and can be constructed with relatively thin and light layers. The soft layer composed of PVAc is typically characterized by a lower residual hydroxyl content (e.g., less than or equal to 16 wt%, less than or equal to 15 wt%, or less than or equal to 12 wt%, or any range disclosed elsewhere), a higher plasticizer content (e.g., greater than or equal to about 48 phr, or greater than or equal to about 70 phr, or any range above), and / or a lower glass transition temperature (e.g., less than 30°C, or less than 10°C, or any range above).

[0064] The polymer sandwich sheets described herein are contemplated to be produced by any suitable method known to those skilled in the art for producing polymer sandwich sheets suitable for use in multilayer panels (e.g., glass laminates). For example, the polymer sandwich sheets are contemplated to be formed by solution casting, compression molding, injection molding, melt extrusion, meltblowing, or any other process known to those skilled in the art for producing and manufacturing polymer sandwich sheets. Furthermore, in embodiments using multiple polymer sandwiches, these multiple polymer sandwiches are contemplated to be formed by co-extrusion, blown film, dip coating, solution coating, knife coating, paddle coating, air knife coating, printing, powder coating, spraying, or other methods known to those skilled in the art. Although all methods of producing polymer sandwich sheets known to those skilled in the art are considered possible methods for producing the polymer sandwich sheets described herein, this application focuses on polymer sandwich sheets produced by extrusion and / or co-extrusion processes. The final multilayer glass panel laminate of this disclosure is formed using methods known in the art.

[0065] During the extrusion process, thermoplastic resins and plasticizers, including any of the resins and plasticizers described above, are typically premixed and fed into the extruder unit. Additives such as colorants and UV inhibitors (in liquid, powder, or granular form) may be used and may be incorporated into the thermoplastic resin or plasticizer before it reaches the extruder unit. These additives are introduced into the thermoplastic polymer resin and, consequently, into the resulting polymer sandwich sheet to enhance certain properties of the polymer sandwich sheet and its performance in the final multilayer glass panel product.

[0066] In an extruder unit, the granules of thermoplastic raw material and plasticizers, including any of the resins, plasticizers, and other additives described above, are further mixed and melted to produce a resin melt with generally uniform temperature and composition. Embodiments of the invention provide a melt temperature of approximately 200°C. Once the melt reaches the end of the extruder unit, it is forced into an extruder die. The extruder die is a component of the extruder unit that imparts its profile to the final polymer sandwich sheet product. The die typically has an opening defined by a lip, which is substantially larger in one dimension than in the vertical dimension. Typically, the die is designed such that the melt flows uniformly from the cylindrical profile exiting the die and into the end profile shape of the product. A variety of shapes can be imparted to the final polymer sandwich sheet through the die, provided a continuous profile exists. Generally, in its most basic sense, extrusion is a process used to produce an object with a fixed cross-sectional profile. This is achieved by pushing or pulling material through a die having the desired cross-section of the final product.

[0067] In some embodiments, a co-extrusion process can be used. Co-extrusion is a method of simultaneously extruding multiple layers of polymer materials. Typically, this type of extrusion utilizes two or more extruders to melt and deliver different thermoplastic melts of varying viscosities or other properties through a co-extrusion die in a stable volumetric throughput to the desired final form. For example, the multilayer sandwich of the present invention (e.g., in the form of a three-layer sandwich) can preferably be co-extruded using a multi-manifold co-extrusion apparatus comprising a first die manifold, a second die manifold, and a third die manifold. The co-extrusion apparatus is operated by simultaneously extruding polymer melt from each manifold through the die and from the opening, wherein the multilayer sandwich is extruded as a composite material of three separate polymer layers. The polymer melt can flow through the die such that a core layer is located between the skin layers, resulting in the manufacture of a three-layer sandwich with the core layer sandwiched between the skin layers. The die opening may include a pair of lips located on either side of the opening. The skin layers may contact the lips, taking into account the positional orientation of the polymer melt. In any case, the sandwich thickness can be varied by adjusting the distance between the die lips located at the die opening.

[0068] The thickness of the multiple polymer layers exiting the extrusion die during co-extrusion is typically controlled by adjusting the relative speed of the melt through the extrusion die and by the size of the individual die lips. According to some embodiments, the total thickness of the multilayer sandwich can be at least about 13 mils, at least about 20 mils, at least about 25 mils, at least about 27 mils, at least about 30 mils, at least about 31 mils and / or not more than about 75 mils, not more than about 70 mils, not more than about 65 mils, not more than about 60 mils, or it can be in the range of about 13 to about 75 mils, about 25 to about 70 mils, or about 30 to 60 mils. When the interlayer comprises two or more polymer layers, the thickness of each layer may be at least about 2, at least about 3, at least about 4, at least about 5, at least about 6, at least about 7, at least about 8, at least about 9, at least about 10 mils and / or no more than about 50, no more than about 40, no more than about 30, no more than about 20, no more than about 17, no more than about 15, no more than about 13, no more than about 12, no more than about 10, no more than about 9 mils. In some embodiments, each layer may have substantially the same thickness, while in other embodiments, one or more layers may have a different thickness than one or more other layers within the interlayer.

[0069] In some embodiments, the interlayer comprises at least three polymer layers, and one or more inner layers may be relatively thin compared to the other outer layers. For example, in some embodiments where the multilayer interlayer is a three-layer interlayer, the innermost layer may have a thickness of no more than about 12, no more than about 10, no more than about 9, no more than about 8, no more than about 7, no more than about 6, or no more than about 5 mils, or it may have a thickness of about 2 to about 12 mils, about 3 to about 10 mils, or about 4 to about 9 mils. In the same or other embodiments, the thickness of each of the outer layers may be at least about 4, at least about 5, at least about 6, at least about 7 mils and / or no more than about 15, no more than about 13, no more than about 12, no more than about 10, no more than about 9, or no more than about 8 mils, or may be in the range of about 2 to about 15, about 3 to about 13, or about 4 to about 10 mils. When the interlayer comprises two outer layers, these layers may have a thickness of at least about 9, at least about 13, at least about 15, at least about 16, at least about 18, at least about 20, at least about 23, at least about 25, at least about 26, at least about 28, or at least about 30 mils, and / or no more than about 73, no more than about 60, no more than about 50, no more than about 45, no more than about 40, or no more than about 35 mils, or a combination of thicknesses within the range of about 9 to about 70 mils, about 13 to about 40 mils, or about 25 to about 35 mils.

[0070] According to some embodiments, the thickness ratio of one of the outer layers to one of the inner layers in a multilayer sandwich can be at least about 1.4:1, at least about 1.5:1, at least about 1.8:1, at least about 2:1, at least about 2.5:1, at least about 2.75:1, at least about 3:1, at least about 3.25:1, at least about 3.5:1, at least about 3.75:1, or at least about 4:1. When the sandwich is a three-layer sandwich having an inner core layer disposed between one pair of outer skin layers, the thickness ratio of one of the skin layers to the core layer can fall within one or more of the above ranges. In some embodiments, the combined thickness ratio of the outer layer to the inner layer may be at least about 2.25:1, at least about 2.4:1, at least about 2.5:1, at least about 2.8:1, at least about 3:1, at least about 3.5:1, at least about 4:1, at least about 4.5:1, at least about 5:1, at least about 5.5:1, at least about 6:1, at least about 6.5:1, or at least about 7:1 and / or no more than about 30:1, no more than about 20:1, no more than about 15:1, no more than about 10:1, no more than about 9:1, or no more than about 8:1.

[0071] The multilayer sandwich described herein may include a generally flat sandwich having substantially the same thickness along the length or longest dimension and / or width or second longest dimension of a sheet. However, in some embodiments, the multilayer sandwich of the present invention may be a conical or wedge-shaped sandwich comprising at least one conical region having a wedge-shaped profile. The conical sandwich has a varying thickness profile along at least a portion of the length and / or width of the sheet, such that, for example, at least one edge of the sandwich has a thickness greater than that of another edge. When the sandwich is a conical sandwich, at least one, at least two, at least three or more individual resin layers may comprise at least one conical region. Conical sandwiches may be particularly useful for head-up display (HUD) panels, for example, in automotive and aircraft applications.

[0072] In view of the above, embodiments of the present invention include a polymer interlayer with improved acoustic properties. The polymer interlayer may be three layers, including a soft core polymer layer, a first hard skin polymer layer, and a second hard skin polymer layer. A core layer is located between the skin layers. The core layer may be formed of a resin comprising polyvinyl acetate (PVAc). For example, the core layer may comprise a hybrid PVAc resin. The first and second skin layers may be formed of PVB, or alternatively, may be formed of PVAc. For example, the skin layer may be formed of a resin substantially composed of PVB. However, the core layer may have a T0 of less than about 20°C. g And tanδ greater than approximately 2.0.

[0073] The tanδ (tan delta) of a material (e.g., a polymer layer) indicates certain acoustic properties of the material and can be obtained from the material's glass transition. Specifically, the tanδ (or loss factor) of a material indicates the effectiveness of its sound damping ability (where a higher tanδ value indicates higher damping ability). The glass transition of a polymer layer is the reversible transition of the material from a hard "glassy" state to a viscous rubbery state; the glass transition temperature is the temperature at which the transition from the glassy state to the rubbery state occurs. At the glass transition state, the polymer layer provides the highest acoustic damping, and the glass transition temperature is used to characterize the sound insulation properties of the polymer. Glass transition temperature (T0) g The temperature modulus (T) can be determined through dynamic mechanical analysis in shear mode (DMA). DMA can be used to measure the storage (elastic) modulus (G') and loss (viscous) modulus (G') in Pascals as a function of temperature of a sample at a given frequency and temperature scan rate. The tanδ of the sample can be calculated based on the ratio of the loss modulus to the storage modulus; in other words, tanδ = G'' / G'. The T of the sample... g It can be determined based on the position of the tanδ peak on a temperature scale in °C.

[0074] Because the polymer layer has a glass transition temperature T g The polymer layer provides the highest acoustic damping, so the tanδ peak can also be used to characterize the acoustic properties of the polymer layer. As mentioned above, generally, the higher the tanδ value (including the tanδ peak value) of the polymer layer, the better its sound insulation properties. Accordingly, when the polymer layer is part of the multilayer sandwich of the present invention (e.g., a three-layer sandwich comprising a soft polymer core layer with an improved tanδ sandwiched between two hard-skin polymer layers) and further used in laminated glass panels (e.g., having a 2.3 mm glass / / laminate / / 2.3 mm glass construction), such glass panels can have beneficial sound insulation properties. This sound insulation property can be referred to as transmission loss, which is measured in decibels (“dB”) for a given frequency or frequency range.

[0075] In various embodiments, the polymer sandwich of the present invention (e.g., a three-layer structure comprising a soft polymer core sandwiched between two hard polymer layers) may include a soft-core PVAc layer exhibiting a glass transition temperature Ti less than about 20°C, less than 19°C, less than 18°C, less than 17°C, less than 16°C, less than 15°C, less than 10°C, less than 5°C, less than 3°C, less than 0°C, less than -3°C, less than -5°C, and / or less than -10°C. g In some embodiments, the glass transition temperature T of the core layer gIt can be -10°C to 20°C, from -10°C to 10°C, from -10°C to 0°C, from -5°C to 5°C, from -3°C to 3°C, or about -2°C, about -1°C, about 0°C, about 1°C and / or about 2°C. Accordingly, in some embodiments, the peak tanδ of the soft core layer of the polymer interlayer of the present invention can be greater than 1.50, greater than 1.50, greater than 1.60, greater than 1.70, greater than 1.80, greater than 1.90, greater than 2.00, greater than 2.10, greater than 2.20, greater than 2.30, greater than 2.40, greater than 2.50, greater than 2.60, greater than 2.70, greater than 2.80, greater than 2.90, greater than 3.00, greater than 3.10, greater than 3.20, greater than 3.30, greater than 3.40, greater than 3.50, greater than 3.60, greater than 3.70, greater than 3.80, greater than 3.90, and / or greater than 4.00. Furthermore, in some embodiments, the peak tanδ of the soft core layer of the polymer interlayer of the present invention can be 1.50 to 4.00, 1.50 to 2.00, 1.80 to 3.8, 2.0 to 3.5 and / or 2.1 to 3.0.

[0076] In various embodiments, the polymer interlayer of the present invention (e.g., a three-layer structure comprising a soft polymer core sandwiched between two hard polymer layers) can itself exhibit a glass transition temperature T less than about 20°C, less than 15°C, less than 10°C, less than 5°C, less than 3°C, less than 0°C, less than -3°C, less than -5°C, and / or less than -10°C. g In some embodiments, the glass transition temperature T of the core layer g The values ​​can be -10°C to 20°C, -10°C to 10°C, 0°C to 10°C, -5°C to 5°C, -3°C to 3°C, or about -5°C, or about -°C, or about -3°C, or about -2°C, about -1°C, about 0°C, about 1°C, about 2°C, about 3°C, about 4°C, and / or about 5°C. Accordingly, in some embodiments, the peak tanδ of the polymer interlayer of the present invention can be greater than 1.20, greater than 1.30, greater than 1.40, greater than 1.50, greater than 1.50, greater than 1.60, greater than 1.70, greater than 1.80, greater than 1.90, and / or greater than 2.00. Furthermore, in some embodiments, the peak tanδ of the polymer interlayer of the present invention can be 1.20 to 2.00, 1.30 to 1.90, 1.30 to 1.80, 1.30 to 1.70, 1.30 to 1.60 and / or 1.40 to 1.60.

[0077] When the polymer interlayer of the present invention is laminated between a pair of glass sheets to form a glass panel, as discussed above (i.e., having a 2.3-mm glass / / interlayer / / 2.3-mm glass configuration), the resulting glass panel can have a sound transmission loss (STL) greater than 30 dB, greater than 31 dB, greater than 32 dB, greater than 33 dB, greater than 34 dB, or greater than 35 dB, measured by weighted average transmission loss at 1000-10000 Hz. In various embodiments, the interlayer of the present invention has a sound insulation of greater than 35 dB, greater than 36 dB, greater than 37 dB, greater than 38 dB, greater than 39 dB, greater than 40 dB, greater than 41 dB, or greater than 42 dB at the coincident frequency of the glass panel (when in a glass panel having a 2.3 mm glass / / interlayer / / 2.3 mm glass configuration and at 20°C) (see definitions below). In some embodiments, the coincidence frequency of the glass panel including the polymer interlayer according to embodiments of the present invention may be 4000-5000Hz or about 4400Hz. In various embodiments, the interlayer of the present invention has sound insulation greater than 35dB, greater than 36dB, greater than 37dB, greater than 38dB, greater than 39dB, greater than 40dB, greater than 41dB, or greater than 42dB at the coincidence frequency of the glass panel from 1000Hz (when in a glass panel having a 2.3mm glass / / interlayer / / 2.3mm glass construction and at 20°C). In various embodiments, the interlayer of the present invention has sound insulation of greater than 38 dB, greater than 39 dB, greater than 40 dB, greater than 41 dB, greater than 42 dB, greater than 43 dB, greater than 44 dB, greater than 45 dB, greater than 46 dB, greater than 47 dB, greater than 48 dB, greater than 49 dB, or greater than 50 dB from the coincidence frequency of the glass panel up to 10,000 Hz (when in a glass panel having a 2.3 mm glass / / interlayer / / 2.3 mm glass construction and at 20°C).

[0078] It is understood that glass has a specific critical or coincident frequency at which the speed of incident sound waves in air matches the speed of the glass bending waves. At the coincident frequency, sound waves are particularly effective at causing the glass to vibrate, and vibrating glass is an effective sound radiator at or near the coincident frequency, as well as at frequencies above or below the coincident frequency. As a result, the glass exhibits a decrease or reduction in sound transmission loss, known as the coincident drop or coincident effect, and the glass becomes transparent to sound.

[0079] The overlap frequency of the glass panels can be represented by the following equation (3):

[0080] f c =c 2 / 2π×[ρ s / B] 1 / 2 (3)

[0081] Where c is the speed of sound in air, ρ s B is the surface density of the glass panel, and B is the bending stiffness of the glass panel. Generally, the coincidence frequency increases as the thickness of the glass panel decreases. For automotive windows, the coincidence frequency is typically in the range of 3150 to 6000 Hz, which falls well within the 2000 to 8000 Hz wind noise frequency range. For laminated building glass (e.g., windows), the coincidence frequency is typically less than about 3150 Hz.

[0082] The aforementioned polymer sandwich with improved acoustic properties can be formed by extruding a first polymer melt to form a soft core layer and extruding a second polymer melt to form first and second hard skin layers. In some embodiments, the first polymer melt is fed by a first extruder (e.g., a core extruder), while the second polymer melt is fed by a second extruder (e.g., a skin extruder), and then split into two streams to form the skin layer. Regardless of the core and skin layers, they are typically co-extruded such that the core layer is located between the first and second skin layers. Notably, the first polymer melt forming the core layer contains PVAc resin and a plasticizer, which, as discussed above, allows the core layer to have a Tc of less than about 20°C. g And tanδ greater than approximately 2.0.

[0083] Therefore, as discussed above and as will be described in more detail in the examples below, the polymer interlayer of the present invention will include improved sound damping characteristics. Furthermore, embodiments may additionally include a method of forming a laminated glass panel with improved acoustic properties. This method may include laminating the aforementioned polymer interlayer between a pair of glass sheets to form a laminated glass panel. Due to the inclusion of the polymer interlayer of the present invention, such a glass panel can have improved sound insulation characteristics, as discussed above. Advantageously, the compositions of the core and skin layers exhibit suitable compatibility with each other to provide sufficient adhesion, thereby promoting bonding of the polymer layers during the manufacture and use of the polymer interlayer. Specifically, in the various embodiments described above, the core layer will be formed of a hybrid PVAc resin (i.e., a PVAc resin having at least 40 wt% acetate content and greater than nominal amounts of hydroxyl and aldehyde content), while the skin layer will consist essentially of PVB. However, a non-nominal amount of PVB in the PVAc resin of the core layer is beneficial for proper adhesion between the core and skin layers.

[0084] Although the above embodiments primarily discuss the three-layer form of the polymer sandwich of the present invention, the polymer sandwich of the present invention can also be in the form of a five-layer sandwich. Such a five-layer sandwich may include a soft core polymer layer, a first hard skin polymer layer, a first buffer layer located between the core and the first skin layer, a second hard skin polymer layer, and a second buffer layer located between the core and the second skin layer. The core layer may be formed of a resin containing PVAc. For example, the core layer may contain a hybrid PVAc resin. Alternatively, the core layer may be formed of a resin composed essentially of PVAc. The first and second skin layers may be formed of PVB, or alternatively, may also be formed of PVAc. For example, the skin layer may be formed of a resin composed essentially of PVB. Furthermore, the buffer layer may include a hybrid PVAc resin. Alternatively, the buffer layer may be formed of a resin composed essentially of PVAc. However, the five-layer sandwich can provide improved sound damping characteristics. For example, the five-layer sandwich can be formed to have the same or similar tanδ peak value and glass transition temperature T as the three-layer polymer sandwich discussed above. g Values. These beneficial properties are discussed in more detail in the following embodiments.

[0085] In some respects, a polymer interlayer with improved acoustic properties comprises: a first polymer layer; a second polymer layer; and a third polymer layer, wherein the first polymer layer is located between the second polymer layer and the third polymer layer, wherein the first polymer layer is formed of a resin comprising polyvinyl acetate (PVAc), and wherein the first polymer layer has a Tc of less than about 20°C. g And a peak tanδ greater than approximately 2.0.

[0086] In other respects, a method for forming a polymer sandwich with improved acoustic properties includes the steps of: (a) extruding a first polymer melt to form a first polymer layer; and (b) extruding a second polymer melt to form a second polymer layer and a third polymer layer; wherein, during the extrusion in steps (a) and (b), the first polymer layer is located between the second polymer layer and the third polymer layer, wherein the first polymer melt comprises a resin containing polyvinyl acetate (PVAc), and wherein the first polymer layer has a Tc of less than about 20°C. g And a peak tanδ greater than approximately 2.0.

[0087] In some respects, the extrusion in steps (a) and (b) is carried out via co-extrusion, wherein the peak tanδ of the first polymer layer is 2.0 to 3.5, and wherein the T of the first polymer layer is... g The temperature ranges from -5℃ to 5℃.

[0088] In some aspects, the peak tanδ of the first polymer layer is between 2.0 and 3.5. In some aspects, the Tg of the first polymer layer... gThe temperature ranges from -5 to 5℃.

[0089] In some aspects, the polymer interlayer comprises: a first polymer layer; a second polymer layer; and a third polymer layer, wherein the first polymer layer is located between the second polymer layer and the third polymer layer, wherein the first polymer layer is formed of a hybrid resin comprising polyvinyl acetate (PVAc), and wherein the first polymer layer has a Tc of less than about 20°C. g And a peak tanδ greater than about 1.5.

[0090] In some aspects, the peak tanδ of the first polymer layer in any polymer sandwich is between 1.5 and 2.0. In some aspects, the Ta of the first polymer layer in any polymer sandwich... g The temperature is -10°C to 10°C, or the T value of the first polymer layer. g The temperature range is 0°C to 10°C. In some aspects, the peak tanδ of any polymer interlayer is greater than 1.3, or the peak tanδ of the polymer interlayer is between 1.3 and 1.8. In some aspects, the Tt of any of the polymer interlayers... g The temperature ranges from 0°C to 10°C.

[0091] In some respects, the first and second polymer layers are essentially composed of polyvinyl butyral (PVB).

[0092] On the other hand, the polymer interlayer includes: a first polymer layer; a second polymer layer; and a third polymer layer, wherein the first polymer layer is located between the second polymer layer and the third polymer layer, wherein the first polymer layer is formed of a resin comprising polyvinyl acetate (PVAc), and wherein the polymer interlayer has a Tc of less than about 20°C. g And a peak tanδ greater than approximately 1.3.

[0093] In some aspects, the peak tanδ of the polymer interlayer is greater than 1.5. In some aspects, the Tg of the polymer interlayer... g It is less than 0℃.

[0094] In some respects, the first polymer layer is substantially composed of polyvinyl acetate (PVAc). In other respects, the second and third polymer layers are adhesive layers comprising hybrid polyvinyl acetate (PVAc).

[0095] In some aspects, the polymer interlayer further includes a fourth polymer layer and a fifth polymer layer, wherein the second polymer layer is located between the first polymer layer and the fourth polymer layer, and wherein the third polymer layer is located between the first polymer layer and the fifth polymer layer. In some aspects, the fourth and fifth polymer layers are skin layers composed essentially of polyvinyl butyral (PVB).

[0096] In some aspects, the resin of the first polymer layer of any polymer sandwich comprises a glycerol-based plasticizer and / or a glycol diester plasticizer. In some aspects, the resin comprises 50 phr to 70 phr of plasticizer. In some aspects, the plasticizer of the first polymer layer of any polymer sandwich comprises glyceryl tribose, or the plasticizer of the first polymer layer comprises a diester having four or more ethylene glycol repeating units, or the plasticizer of the first polymer layer comprises polyethylene glycol bis-(2-ethylhexanoate), or the plasticizer of the first polymer layer comprises molecules with an oxygen-to-carbon ratio of at least 0.32, or the plasticizer of the first polymer layer comprises a glycol diester, and wherein the plasticizer has a molecular weight of at least 420 Daltons, or the plasticizer of the first polymer layer has a molecular weight derived from the dispersion solubility parameter δ. d Polar solubility parameter δ p and hydrogen bond solubility parameter δ h The total solubility parameter δ, which is composed of the contributions of the total solubility parameter δ, tot Among them, the polar solubility parameter δ p and hydrogen bond solubility parameter δ h The contribution relative to the total solubility parameter δ tot The ratio is at least 0.365.

[0097] In some respects, the T of the first polymer layer of any polymer sandwich g T is less than that of both the second polymer layer and the third polymer layer. g .

[0098] In some respects, the resin of any polymer interlayer contains 40 wt% to 80 wt% acetate, 5 wt% to 20 wt% hydroxyl content and 20 wt% to 40 wt% aldehyde content, or the resin contains at least 50 wt% acetate, or the resin contains 10 wt% to 15 wt% hydroxyl content, or the resin contains 10 wt% to 45 wt% aldehyde content.

[0099] In some respects, the thickness of any of the polymer interlayers is generally constant along the length of the polymer interlayer. In other respects, the thickness of any of the polymer interlayers varies along the length of the polymer interlayer, such that the polymer interlayer has a wedge shape.

[0100] Example 1

[0101] Two polymer sheets were formed, and dynamic mechanical analysis (DMA) was used to determine the tanδ values ​​of the sheets over a specific temperature range. The first sheet, “EX1-S1”, was formed using a 200K–700K Dalton PVAc monopolymer resin with 48 phr of glyceryl tribose plasticizer. The second sheet, “EX1-S2”, was formed using a 50,000–600,000 Dalton PVB resin (containing 10.5 wt% PVOH, 2.0 wt% PVAc, and 87.5 wt% PVB) with 75 phr of triethylene glycol di-(2-ethylhexanoate) plasticizer. Each sheet in EX1-S1 and EX1-S2 was produced from the resin via compression molding, which involved forming the sheet using a steam hot press. Tanδ measurements were performed on the sheet samples after drying overnight in a desiccator. This test used dynamic mechanical analysis (DMA) in torsional and tensile modes. Samples were tested using a rheological solids analyzer at an oscillation frequency of 1 Hz over a temperature range of -40 to 20 °C. Frequency dependence parameters were obtained using time-temperature superposition, where for each sample, DMA was performed from 0.3 rad / s to 300 rad / s at -40 °C, -20 °C, -10 °C, 0 °C, 10 °C, and 20 °C.

[0102] Figure 3 The diagram shows the resulting tanδ plots for each of two polymer layers, sheets EX1-S1 and EX1-S2. As shown, sheet EX1-S1, containing PVAc resin and glyceryl tribose plasticizer, exhibits a T1 tanδ plot. g A peak tanδ of 2.9 is produced at -3℃. This loss factor (such as the tanδ value and T) g The image shown is an improvement on the polymer layer of sheet EX1-S2, which contains standard PVB and triethylene glycol di-(2-ethylhexanoate) plasticizer. Specifically, as shown, sheet EX1-S2 in T g A peak tanδ of only 1.3 was generated at -1℃. Therefore, compared to similar PVB formulations (i.e., sheet EX1-S2), the polymer layer containing PVAc and glyceryl tartrate plasticizer (i.e., sheet EX1-S1) exhibits a peak tanδ of only 1.3 at the same or near-1℃. g The following shows a peak tanδ exceeding 100% and / or an increase in the loss factor.

[0103] Example 2

[0104] Three polymer sheets were formed, and dynamic mechanical analysis (DMA) was used to determine the tanδ value of the sheets over a specific temperature range. The first sheet, “EX2-S1”, was formed from 500K Dalton PVAc monopolymer resin and 60 phr of poly(ethylene glycol) bis(2-ethylhexanoate) plasticizer. The second sheet, “EX2-S2”, was also formed from 500K Dalton PVAc monopolymer resin and 60 phr of poly(ethylene glycol) bis(2-ethylhexanoate) plasticizer. Finally, the third sheet, “EX2-S3”, was formed from 50,000-600,000 Dalton PVB resin (containing 10.5 wt% PVOH, 2.0 wt% PVAc, and 87.5 wt% PVB) and 75 phr of triethylene glycol bis(2-ethylhexanoate) plasticizer. Each sheet in EX2-S1, EX2-S2, and EX2-S3 was produced from resin via compression molding, which involves forming the sheet using a steam hot press. Tanδ measurements were performed on the sheet samples after drying overnight in a desiccator. This test used dynamic mechanical analysis in torsional and tensile modes (DMA). Samples were tested using a rheological solids analyzer at an oscillation frequency of 1 Hz over a temperature range of -20 to 60 °C. Frequency dependence parameters were obtained using a time-temperature superposition, where, for each sample, DMA was performed from 0.3 rad / s to 300 rad / s at -20 °C, -10 °C, 0 °C, 10 °C, 20 °C, 30 °C, 40 °C, and 60 °C.

[0105] Figure 4 The image shows the obtained tanδ curves for each of the three polymer layers, sheets EX2-S1, EX2-S2, and EX2-S3. As shown, sheets EX2-S1 and EX2-S2, both containing PVAc resin and poly(ethylene glycol) bis(2-ethylhexanoate) plasticizer, exhibit tanδ curves at T0. g A peak tanδ of approximately 2.2 is produced at approximately -1°C. This loss factor (such as tanδ value and T) g The sheet shown is an improvement on the polymer layer of sheet EX2-S3, which contains standard PVB and triethylene glycol di-(2-ethylhexanoate) plasticizer. Specifically, as shown, sheet EX2-S3 in T g At -1°C, a peak tanδ of only about 1.1 is produced. Therefore, compared to similar PVB formulations (i.e., sheet EX2-S3), polymer layers containing PVAc and poly(ethylene glycol) bis(2-ethylhexanoate) plasticizer (i.e., sheets EX2-S1 and EX2-S2) exhibit a peak tanδ of only about 1.1 at the same or near-1°C. g The following shows a peak tanδ exceeding 100% and / or an increase in the loss factor.

[0106] After obtaining the tanδ curves, simulations were performed on two polymer layers, EX2-S1 and EX2-S3, to obtain sound loss transmission (STL) data when the polymer layers are included within a laminated glass panel. Specifically, the polymer layers were modeled as the core layer in a three-layer multilayer (i.e., skin / core / skin) sandwiched between a pair of glass plates. An STL model was built and simulated using the finite element software tool COMSOL. The STL model is a two-dimensional model, as shown below. Figure 5 As shown. In this model, the glass panel comprises a composite of "2.3mm glass plate - 0.355mm skin (PVB) - 0.11mm core layer - 0.355mm skin (PVB) - 2.3mm glass plate", embedded in an infinite air space (created by applying a perfectly matched layer). The frequency dependence parameters of both EX2-S1 (PVAc) and EX2-S3 (PVB), measured by DMA, are applied to this model. (Diffuse sound STL) d The STL of the field is calculated by the following equation (4):

[0107]

[0108] in, It is the sound intensity transmission coefficient, θ is the angle of the incident plane wave, and p t It is the transmitted sound pressure, p i This is the incident sound pressure. It is assumed that the incident angle is uniformly distributed between 0° and 78° (in radians 1–1.361). The integral was calculated using MATLAB software based on Simpson's law.

[0109] The obtained simulated STL data in Figure 6 The results are illustrated graphically. The STL data show that the coincidence frequency of the laminated glass panel with the PVAc core (EX2-S1) shifts to a lower frequency compared to the laminated glass panel with the PVB core (EX2-S3). This is likely because PVAc is generally stiffer than PVB above 100Hz. In any case, the STL performance of the laminated glass panel with the PVAc core is lower at low frequencies (i.e., below 4400Hz). However, at frequencies higher than the coincidence frequency of the laminated glass panel with the PVB core (EX2-S3), the STL of the laminated glass panel with the PVAc core (EX2-S1) shows an improvement of 2+ dB compared to the laminated glass panel with the PVB core. This result is likely due to the fact that both the damping and stiffness of PVAc are greater than those of PVB.

[0110] Example 3

[0111] Four polymer sheets were formed, and dynamic mechanical analysis (DMA) was used to determine the tanδ value of the sheets over a specific temperature range. The first sheet, “EX3-S1”, was formed from 500K Dalton PVAc monopolymer resin and 60 phr of poly(ethylene glycol) bis(2-ethylhexanoate) plasticizer. The second sheet, “EX3-S2”, was formed from 500K Dalton PVAc monopolymer resin and 60 phr of poly(ethylene glycol) bis(2-ethylhexanoate) plasticizer. The third sheet, “EX3-S3”, was formed from 500K Dalton PVAc monopolymer resin and 62.5 phr of poly(ethylene glycol) bis(2-ethylhexanoate) plasticizer. Finally, the fourth sheet, “EX3-S4,” was formed from 50,000 to 600,000 Daltons of PVB resin (containing 10.5 wt% PVOH, 2.0 wt% PVAc, and 87.5 wt% PVB) with 75 phr of triethylene glycol di-(2-ethylhexanoate) plasticizer. Each of the sheets, EX3-S1, EX3-S2, EX3-S3, and EX3-S4, was produced from the resin via compression molding, which involved forming the sheet using a steam hot press. Tanδ measurements were performed on the sheet samples after drying overnight in a desiccator. This test used dynamic mechanical analysis (DMA) in torsional and tensile modes. Samples were tested using a rheological solids analyzer at an oscillation frequency of 1 Hz over a temperature range of -20 to 60 °C. Frequency-dependent parameters were obtained using a time-temperature superposition method, where for each sample, DMA was performed from 0.3 rad / s to 300 rad / s at -20°C, -10°C, 0°C, 10°C, 20°C, 30°C, 40°C, and 60°C.

[0112] Figure 7 The table shows the obtained tanδ curves for each of the four polymer layers, sheets EX3-S1, EX3-S2, EX3-S3, and EX3-S4. As shown, sheets EX3-S1 and EX3-S2, both containing PVAc resin and 60 phr of poly(ethylene glycol) bis(2-ethylhexanoate) plasticizer, were subjected to a T1 temperature of approximately -1°C. g A peak tanδ of approximately 2.2 is produced. The EX3-S3 sheet, containing PVAc resin and 62.5 phr of poly(ethylene glycol) bis(2-ethylhexanoate) plasticizer, shows a slightly lower T value at approximately -2°C. g A slightly larger peak tanδ of approximately 2.3 is produced. The measured loss factors (such as tanδ value and T) g Each of the following (shown) represents an improvement on the polymer layer of sheet EX3-S4 containing standard PVB and triethylene glycol di-(2-ethylhexanoate) plasticizer. Specifically, as shown, sheet EX3-S4 is subjected to a T at -1°C. gThe peak tanδ was only about 1.1. Therefore, compared to similar PVB formulations (i.e., sheet EX3-S4), polymer layers containing PVAc and poly(ethylene glycol) bis(2-ethylhexanoate) plasticizer (i.e., sheets EX3-S1, EX3-S2, and EX3-S3) showed a peak tanδ of only about 1.1. g The following shows a peak tanδ exceeding 100% and / or an increase in the loss factor.

[0113] After obtaining the tanδ diagram, simulations were performed on three polymer sheets, namely EX3-S1, EX3-S3, and EX3-S4, to obtain sound loss transmission (STL) data when the polymer sheets were included in a laminated glass panel. Specifically, using the STL model described in Example 2 above, the polymer sheets were simulated as part of the laminated glass panel, and the resulting simulated STL data is shown below. Figure 8 middle.

[0114] The STL data shows that the laminated glass panel with a PVAc core containing 60 phr of plasticizer (EX3-S1) has an STL loss of less than 4400 Hz compared to the laminated glass panel with a PVB core (EX3-S4), while the laminated glass panel with a PVAc core containing 62.5 phr of plasticizer (EX3-S3) does not exhibit this loss. This result is likely due to the fact that 62.5 phr of PVAc is softer than 60 phr of PVAc, causing the coincidence frequency of the laminated glass panel with PVAc and 62.5 phr of plasticizer (EX3-S3) to shift to a higher frequency. This shift results in the STL performance of the laminated glass panel with PVAc and 62.5 phr of plasticizer (EX3-S3) at low frequencies (below the coincidence frequency) being similar to that of the laminated glass panel with a PVB core (EX3-S4).

[0115] At 4400 Hz and above, the laminated glass panel with PVAc and 62.5 phr plasticizer (i.e., EX3-S3) provides a 2 dB improvement compared to the laminated glass panel with a PVB core layer (i.e., EX3-S4). This result is likely due to the significantly higher damping characteristics of PVAc compared to PVB. For frequencies above 4400 Hz, the STL curve of the 60 phr plasticizer core layer (i.e., EX3-S1) overlaps with that of the laminated glass panel with PVAc and 62.5 phr plasticizer (i.e., EX3-S3). This result is likely due to the higher damping of PVAc with 62.5 phr plasticizer compared to PVAc with 60 phr plasticizer in this frequency range, and the higher damping of the laminated glass panel with PVAc with 62.5 phr plasticizer (i.e., EX3-S3) compensates for the STL loss caused by the reduced modulus.

[0116] Example 4

[0117] As provided in Table 1 below, eight exemplary hybrid PVAc resin samples (“HRS”) 1-8 were formed, each with different amounts of acetate, hydroxyl, and aldehyde content. For each sample, the percentage of hydrolysis used to form the sample is also provided.

[0118] Table 1

[0119] sample hydrolysis% wt%PVAc wt% PVB wt% PVOH HRS-1 17.4 88.7 4.4 6.9 HRS-2 21.5 84.7 9 6.3 HRS-3 31.4 76 16.5 7.5 HRS-4 62.1 44.6 47.5 7.9 HRS-5 61.0 45.4 47.5 7 HRS-6 33.4 72.8 22.5 4.7 HRS-7 37.2 70 23.2 6.8 HRS-8 47.0 59.9 33.9 6.2

[0120] Sub-instance 4A

[0121] Three polymer sheets were formed, and dynamic mechanical analysis (DMA) was used to determine the tanδ value of the sheets over a specific temperature range. The first sheet, “EX4A-S1”, was formed from HRS-2 sample resin with 63.4 phr of poly(ethylene glycol) bis(2-ethylhexanoate) plasticizer. The second sheet, “EX4A-S2”, was formed from HRS-4 sample resin with 59.5 phr of triethylene glycol bis(2-ethylhexanoate) plasticizer. Finally, the third sheet, “EX4A-S3”, was formed from 50,000 to 600,000 Dalton PVB resin (containing 10.5 wt% PVOH, 2.0 wt% PVAc, and 87.5 wt% PVB) with 75 phr of triethylene glycol bis(2-ethylhexanoate) plasticizer. Each sheet in EX4A-S1, EX4A-S2, and EX4A-S3 was produced from resin via compression molding, which involves forming the sheet using a steam hot press. Tanδ measurements were performed on the sheet samples after drying overnight in a desiccator. This test used dynamic mechanical analysis (DMA) in torsional and tensile modes. Samples were tested using a rheological solids analyzer at an oscillation frequency of 1 Hz over a temperature range of -20 to 60 °C. Frequency dependence parameters were obtained using time-temperature superposition, where DMA was performed for each sample from 0.3 rad / s to 300 rad / s at -20 °C, -10 °C, 0 °C, 10 °C, 20 °C, 30 °C, 40 °C, and 60 °C.

[0122] Figure 9 The image shows the tanδ curves for each of the three polymer layers, sheets EX4A-S1, EX4A-S2, and EX4A-S3. As shown, sheet EX4A-S1 (formed from hybrid PVAc resin) exhibits tanδ curves at T... g A peak tanδ of approximately 1.88 is generated at approximately -6°C, while the EX4A-S2 sheet (also formed from hybrid PVAc resin) exhibits a slightly higher tanδ at approximately -0.4°C. g A slightly smaller peak tanδ of approximately 1.66 is produced. The loss factor for each measurement (e.g., tanδ value and T) gThe sheet shown is an improvement on the polymer layer of sheet EX4A-S3, which contains standard PVB resin and triethylene glycol di-(2-ethylhexanoate) plasticizer. Specifically, as shown, sheet EX4A-S3 is subjected to a T at -1°C. g The resulting peak tanδ is only about 1.1. Therefore, compared to the same or close T, g Similar PVB formulations (i.e. sheet EX4A-S3), polymer layers containing hybrid PVAc with poly(ethylene glycol) bis(2-ethylhexanoate) or triethylene glycol bis(2-ethylhexanoate) plasticizers (i.e. sheets EX4A-S1 and EX4A-S2) showed an increase in peak tanδ and / or loss factor.

[0123] although Figure 9 Not shown, but two additional polymer sheets were generated using HRS-2 and HRS-4 resin samples and tested in the same manner as described above. Specifically, the fourth sheet, “EX4A-S4”, was formed from the HRS-2 sample resin with 68.7 phr of poly(ethylene glycol) bis(2-ethylhexanoate) plasticizer. The fifth sheet, “EX4A-S5”, was formed from the HRS-4 sample resin with 55.6 phr of triethylene glycol bis(2-ethylhexanoate) plasticizer. Each sheet was tested using the DMA method described above. The EX4A-S4 sheet was tested at approximately -7°C using a T... g A tanδ peak of approximately 1.8 is produced at approximately 1°C. EX4A-S5 sheet exhibits this peak at a temperature of approximately 1°C. g A tanδ peak of approximately 1.64 was generated. Therefore, EX4A-S4 and EX4A-S5 sheets confirm that the hybrid PVAc polymer layer exhibits improved tanδ peak value and / or loss factor value compared to the standard PVB formulation.

[0124] Sub-instance 4B

[0125] Three three-layer polymer sandwiches were formed and tested using the DMA method described in more detail below to determine the tanδ values ​​of the sandwiches. Two polymer sandwiches comprise a core layer formed from the hybrid PVAc sample described above in Example 4B. Specifically, a first polymer sandwich “EX4B-S1” was laminated using a core layer composed of the HRS-4 sample resin and 59.5 phr of triethylene glycol di-(2-ethylhexanoate) plasticizer. The core layer was formed to a thickness of approximately 18 mm. Each skin layer of EX4B-S1 comprised a PVB resin (containing 21.1 wt% PVOH, 2.0 wt% PVAc, and 87.5 wt% PVB) and 36.5 phr of triethylene glycol di-(2-ethylhexanoate) plasticizer. The thickness of each skin layer was approximately 0.32 mm. Similarly, a second polymer sandwich “EX4B-S2” was laminated using a core layer composed of the HRS-4 sample resin and 55.6 phr of triethylene glycol di-(2-ethylhexanoate) plasticizer. The core layer is formed to a thickness of approximately 18 mm. Each skin layer of EX4B-S2 comprises PVB resin (containing 18.7 wt% PVOH, 2.0 wt% PVAc, and 87.5 wt% PVB) and 36.5 phr of triethylene glycol di-(2-ethylhexanoate) plasticizer. The thickness of each skin layer is approximately 0.32 mm. Furthermore, a third polymer interlayer, “EX4B-S3,” is laminated using a core layer composed of PVB resin (containing 10.5 wt% PVOH, 2.0 wt% PVAc, and 87.5 wt% PVB). The core layer is formed to a thickness of approximately 11 mm. Each skin layer of EX4B-S3 comprises PVB resin (containing 18.7 wt% PVOH, 2.0 wt% PVAc, and 87.5 wt% PVB) and 38 phr of triethylene glycol di-(2-ethylhexanoate) plasticizer. The thickness of each skin layer is approximately 0.35 mm.

[0126] Each of the polymer sandwich layers EX4B-S1-EX4B-S3 was tested using DMA to determine the tanδ value of the sandwich layer over a specific temperature range. Tanδ measurements were performed on sandwich samples dried overnight in a desiccator. The test used DMA in torsion and tensile modes. Samples were tested using a rheological solids analyzer at an oscillation frequency of 1 Hz over a temperature range of -20 to 60 °C. Frequency dependence parameters were obtained using time-temperature superposition, where DMA was performed for each sample at -20 °C, -10 °C, 0 °C, 10 °C, 20 °C, 30 °C, 40 °C, and 60 °C, from 0.3 rad / s to 300 rad / s.

[0127] The tanδ curves of each of the three obtained three-layer polymer sandwiches EX4B-S1-EX4B-S3 are shown in the figure. Figure 10 and 11 In particular, the tanδ curves of EX4B-S1 and EX4B-S3 are shown in... Figure 10In the middle, the tanδ curves of EX4B-S1 and EX4B-S2 are shown in Figure 11 In the middle. For example Figure 10 As shown, the sandwich layer EX4B-S1 (formed from a core layer containing hybrid PVAc resin) is subjected to a T at approximately 3°C. g A peak tanδ of approximately 1.59 was generated, while the sandwich layer EX4B-S3 (formed from a core layer containing standard PVB resin) showed a peak at approximately 4°C. g A peak tanδ of approximately 1.17 is generated. Therefore, compared to sandwich layers formed with a core layer containing standard PVB, sandwich layers formed with a core layer containing hybrid PVAc show lower measured loss factors (such as tanδ value and T). g The three-layer sandwich (shown) is an improvement. Specifically, compared to the three-layer sandwich with a standard PVB core (i.e., sandwich EX4B-S3), the three-layer sandwich with a core containing a hybrid PVAc (i.e., sandwich EX4B-S1) performs better at the same or near T. g The following shows an increase in peak tanδ and / or loss factor.

[0128] Turn Figure 11 As discussed above, this figure reproduces the tanδ curve of the EX4B-S1 sandwich (formed by a core layer containing hybrid PVAc resin HRS-4 and a triethylene glycol di-(2-ethylhexanoate) plasticizer at 59.5 phr) and shows the tanδ curve of the EX4B-S2 sandwich (formed by a core layer containing hybrid PVAc resin HRS-4 and a triethylene glycol di-(2-ethylhexanoate) plasticizer at 55.6 phr). Therefore, the EX4B-S1 sandwich has slightly more plasticizer in its core layer than the EX4B-S2 sandwich. As shown, the EX4B-S1 sandwich exhibits a T1 at approximately 3°C. g The lower layer produces a tanδ peak of approximately 1.59, while the interlayer EX4B-S2 shows a peak at approximately 9°C. g A peak tanδ of approximately 1.37 is generated. Therefore, compared to sandwich layers formed with a core layer containing a hybrid PVAc with a smaller amount of plasticizer, the measurement loss factors (such as tanδ value and T) of sandwich layers formed with a core layer containing a hybrid PVAc with a larger amount of plasticizer are significantly lower. g The three-layer sandwich (i.e., sandwich EX4B-S1) with a core layer containing hybrid PVAc and 59.5 phr plasticizer is an improvement, compared to the three-layer sandwich (i.e., sandwich EX4B-S2) with a core layer containing hybrid PVAc and 55.6 phr plasticizer. g The following shows an increase in peak tanδ and / or loss factor.

[0129] Sub-instance 4C

[0130] After obtaining the tanδ curves of the EX4A-S2 and EX4A-S3 sheets described in Sub-Example 4A, the sheets are simulated to obtain sound loss transmission (STL) data for the case where the polymer from the polymer sheet is contained within the laminated glass panel. Specifically, the polymer from the polymer sheet is generally simulated as part of the laminated glass panel using the STL model described in Example 2 above. The frequency dependence parameters of the EX4A-S2 and EX4A-S3 sheets, measured by DMA in Sub-Example 4A, are applied to each model. Figure 12-15 The resulting simulated STL data is shown.

[0131] More specifically, a first simulation, "EX4C-S1," was performed using polymers from EX4A-S2 sheets to form the core layer of the three polymer interlayers included in the simulated laminated glass panel. The core layer was modeled with a thickness of 0.22 mm. The skin layers of the three polymer interlayers were modeled as comprising standard PVB resin (containing 21.1 wt% PVOH, 2.0 wt% PVAc, and 87.5 wt% PVB) and 36.5 phr of triethylene glycol di-(2-ethylhexanoate) plasticizer. Each skin layer was modeled with a thickness of 0.3 mm. A second simulation, "EX4C-S2," was performed with the same parameters as EX4C-S1, except that the core layer was modeled with a thickness of 0.18 mm, and each skin layer was modeled with a thickness of 0.32 mm. A third simulation, "EX4C-S3," was performed using polymers from EX4A-S3 sheets to form the core layer of the three polymer interlayers included in the simulated laminated glass panel. The core layer was modeled with a thickness of 0.11 mm. The skin of the three-layer polymer interlayer was modeled as comprising standard PVB resin (including 18.7 wt% PVOH, 2.0 wt% PVAc, and 87.5 wt% PVB) with 38 phr of triethylene glycol di-(2-ethylhexanoate) plasticizer. Each skin layer was modeled with a thickness of 0.355 mm. Except as provided in this paragraph, the simulation models for EX4C-S1, EX4C-S2, and EX4C-S3 are consistent with the STL models described above in Example 2. The simulation curves of the STL data for EX4C-S1, EX4C-S2, and EX4C-S3 are shown in... Figure 12 and 13 As shown in the image.

[0132] Finally, except that the skin of the three-layer polymer interlayer was modeled as containing standard PVB resin (containing 22.3 wt% PVOH, 2.0 wt% PVAc and 87.5 wt% PVB) with 34.7 phr of triethylene glycol di-(2-ethylhexanoate) plasticizer, a fourth simulation, “EX4C-S4”, was performed with the same parameters as EX4C-S2 described above. Except as provided in this paragraph, the simulation model for EX4C-S4 is consistent with the STL model described above in Example 2. The simulation curves of the STL data for EX4C-S2, EX4C-S3, and EX4C-S4 are shown in... Figure 14 and 15 As shown in the image.

[0133] The STL data shows that laminated glass panels with hybrid PVAc layers (EX4C-S1, EX4C-S2, and EX4C-S4) in the core layer provide improved sound damping compared to laminated glass panels with a standard PVB core layer (EXC4-S3). For more details, see [reference needed]. Figure 12 Each laminated glass panel exhibits substantially identical acoustic damping characteristics at frequencies below 4400 Hz. However, glass panels with hybrid PVAc in the core layer (i.e., EX4C-S1 and EX4C-S2) offer an improvement over laminated glass panels with a standard PVB core layer (i.e., EXC4-S3). Figure 13 The STL difference between the laminated glass panels is shown. As shown, for frequencies above 4400Hz, the EX4C-S1 glass panel provides an improvement of approximately 0.6 to 1.1 dB compared to the EX4C-S3 glass panel. For frequencies above 4400Hz, the EX4C-S2 glass panel provides an improvement of approximately 1.1 to 2.6 dB compared to the EX4C-S3 glass panel.

[0134] Similarly, refer to Figure 14 Each laminated glass panel exhibits substantially identical acoustic damping characteristics at frequencies below 4400 Hz. However, glass panels with hybrid PVAc in the core layer (i.e., EX4C-S2 and EX4C-S4) offer an improvement over laminated glass panels with a standard PVB core layer (i.e., EXC4-S3). Figure 15 The STL difference between the laminated glass panels is shown. As shown, for frequencies above 4400Hz, the EX4C-S2 glass panel provides an improvement of approximately 1.1 to 2.6 dB compared to the EX4C-S3 glass panel. For frequencies above 4400Hz, the EX4C-S4 glass panel provides an improvement of approximately 1.6 to 2.2 dB compared to the EX4C-S3 glass panel.

[0135] Sub-instance 4D

[0136] The five-layer polymer interlayer “EX4D-S1” was formed and tested using the DMA method described in more detail below to determine the tanδ value of the interlayer. The EX4D-S1 interlayer was formed together with a core layer composed primarily of PVAc. The core layer had a thickness of approximately 0.05 mm. The EX4D-S1 interlayer included a pair of skin layers located on either side of the core layer. The skin layers were composed primarily of PVB, and each skin layer had a thickness of approximately 0.10 mm. The EX4D-S1 interlayer also included a pair of adhesive layers, each located between the core layer and one skin layer. The adhesive layers were composed of HRS-2 sample resin (provided in Table 1), and each adhesive layer had a thickness of approximately 0.05 mm. Each polymer layer of the EX4D-S1 interlayer was plasticized with poly(ethylene glycol) bis(2-ethylhexanoate).

[0137] The tanδ value of the five-layer polymer sandwich EX4D-S1 was determined using DMA testing over a specific temperature range. Tanδ measurements were performed on sandwich samples dried overnight in a desiccator. The test employed DMA in both torsional and tensile modes. Samples were tested using a rheological solids analyzer at an oscillation frequency of 1 Hz over a temperature range of -20 to 60 °C. Frequency dependence parameters were obtained using time-temperature superposition, where DMA was performed for each sample at -20 °C, -10 °C, 0 °C, 10 °C, 20 °C, 30 °C, 40 °C, and 60 °C, from 0.3 rad / s to 300 rad / s.

[0138] Figure 16 The figure shows the tanδ curves obtained for each of the five-layer polymer sandwich EX4D-S1 and the aforementioned EX4B-S3 (a standard three-layer sandwich formed essentially of PVB). As shown, the five-layer sandwich EX4D-S1 at approximately -3°C... g The standard sandwich EX4B-S3 (formed with a core layer containing standard PVB resin) produces a peak tanδ of approximately 1.53, while the standard sandwich EX4B-S3 produces a peak tanδ of approximately 4°C at a Tt. g A peak tanδ of approximately 1.17 is generated. Therefore, the measured loss factors (such as tanδ value and T) of the sandwich layer formed by the five-layer sandwich (with a PVAc core layer, a hybrid PVAc adhesive layer, and a PVB skin layer) are... g (As shown) This represents an improvement in loss factor compared to a standard three-layer sandwich (with a core and skin layer containing PVB). Specifically, the five-layer sandwich at the same or close T... g The following shows an increase in peak tanδ and / or loss factor relative to the three-layer sandwich.

[0139] While the invention has been disclosed in conjunction with a description of certain embodiments, including those currently considered preferred embodiments, the detailed description is intended to be illustrative and should not be construed as limiting the scope of this disclosure. As will be understood by those skilled in the art, embodiments other than those described in detail herein are also covered by the invention. Modifications and variations may be made to the described embodiments without departing from the spirit and scope of the invention.

[0140] It should also be understood that any range, value, or characteristic given for any single component of this disclosure may be used interchangeably with any range, value, or characteristic given for any other component of this disclosure, where compatible, to form embodiments with defined values ​​for each component, as given throughout this document. For example, polymer layers may be formed that include, in addition to any given range of residual hydroxyl content, any given range of plasticizer content, forming, where appropriate, a number of arrangements within the scope of this invention, but this would be difficult to list.

Claims

1. A polymer sandwich with improved acoustic properties, the polymer sandwich comprising: First polymer layer; Second polymer layer; as well as The third polymer layer, The first polymer layer is located between the second polymer layer and the third polymer layer, wherein the first polymer layer is formed of a resin containing polyvinyl acetate, the polyvinyl acetate being a homopolymer formed by free radical polymerization of vinyl acetate monomers, the polyvinyl acetate-containing resin containing glycerol plasticizer and / or ethylene glycol diester plasticizer, and wherein the first polymer layer has a T0 of less than 20°C. g And peaks with tanδ greater than 1.5, The polymer interlayer has a peak tanδ greater than 1.

3. The peak tanδ is calculated based on the ratio of viscous modulus to elastic modulus. Wherein the first polymer layer T g T is less than that of both the second polymer layer and the third polymer layer. g .

2. The polymer interlayer according to claim 1, wherein the first polymer layer is formed of a resin comprising hybrid polyvinyl acetate, the hybrid polyvinyl acetate having an acetate content of at least 40 wt% and a hydroxyl content and an aldehyde content of more than 4 wt%.

3. The polymer interlayer according to claim 1, wherein the polymer interlayer has a T0 of less than 20°C. g .

4. The polymer interlayer according to claim 1, wherein the peak tanδ of the first polymer layer is 2.0 to 3.

5.

5. The polymer interlayer according to claim 2, wherein the peak tanδ of the first polymer layer is 1.5 to 2.

0.

6. The polymer interlayer according to claim 1, wherein the first polymer layer has a T0 of -5°C to 5°C. g Or wherein the first polymer layer has a T0 of -10°C to 10°C g Or wherein the first polymer layer has a T0 of 0°C to 10°C g Or, wherein the polymer interlayer has a T value of less than 0°C. g Or wherein the polymer interlayer has a T0 of 0°C to 10°C g .

7. The polymer interlayer of claim 1, wherein the resin comprising polyvinyl acetate comprises a plasticizer of the first polymer layer at 50 phr to 70 phr, or wherein the plasticizer of the first polymer layer comprises glyceryl tribaniate, or wherein the plasticizer of the first polymer layer comprises a diester having four or more ethylene glycol repeating units, or wherein the plasticizer of the first polymer layer comprises molecules with an oxygen-to-carbon ratio of at least 0.32, or wherein the plasticizer of the first polymer layer comprises an ethylene glycol diester, and wherein the ethylene glycol diester has a weight-average molecular weight of at least 420 Daltons, or wherein the plasticizer of the first polymer layer has a composition derived from the dispersion solubility parameter δ. d Polar solubility parameter δ p and hydrogen bond solubility parameter δ h The total solubility parameter δ, which is composed of the contributions of the total solubility parameter δ, tot The polar solubility parameter δ p and the hydrogen bond solubility parameter δ h The contribution relative to the total solubility parameter δ tot The ratio is at least 0.

365.

8. The polymer interlayer according to claim 1, wherein the resin comprising polyvinyl acetate comprises 40wt%-80wt% acetate content, 5wt%-20wt% hydroxyl content and 20wt%-40wt% aldehyde content.

9. The polymer interlayer according to claim 1, wherein the first polymer layer is composed of polyvinyl acetate.

10. The polymer interlayer according to claim 1, wherein the second polymer layer and the third polymer layer are adhesive layers comprising hybrid polyvinyl acetate, wherein the hybrid polyvinyl acetate has an acetate content of at least 40 wt% and a hydroxyl content and an aldehyde content of more than 4 wt%.

11. The polymer interlayer of claim 1, further comprising a fourth polymer layer and a fifth polymer layer, wherein the second polymer layer is located between the first polymer layer and the fourth polymer layer, and wherein the third polymer layer is located between the first polymer layer and the fifth polymer layer.

12. The polymer interlayer according to claim 11, wherein the fourth polymer layer and the fifth polymer layer are skin layers composed of poly(vinyl butyral).

13. A method for forming a polymer sandwich with improved acoustic properties, the method comprising the steps of: (a) Extruding the first polymer melt to form a first polymer layer; as well as (b) Extruding the second polymer melt to form a second polymer layer and a third polymer layer; During the extrusion in steps (a) and (b), the first polymer layer is located between the second polymer layer and the third polymer layer. The first polymer melt comprises a resin, the resin including polyvinyl acetate, the polyvinyl acetate being a homopolymer formed by free radical polymerization of vinyl acetate monomers, the resin including a glycerol-based plasticizer and / or a glycol diester plasticizer, wherein the first polymer layer has a Tg of less than 20°C. g And a peak tanδ greater than 2.0, wherein the polymer interlayer has a peak tanδ greater than 1.

3. The peak tanδ is calculated based on the ratio of viscous modulus to elastic modulus. Wherein the first polymer layer T g T is less than that of both the second polymer layer and the third polymer layer. g .

14. The method of claim 13, wherein the extrusion in steps (a) and (b) is performed via co-extrusion, wherein the peak tanδ of the first polymer layer is 2.0 to 3.5, and wherein the Ta of the first polymer layer is... g The temperature ranges from -5℃ to 5℃.

15. The method of claim 13, wherein the resin comprises a plasticizer of 50 phr to 70 phr in the first polymer layer, or wherein the plasticizer of the first polymer layer comprises glyceryl tartrate, or wherein the plasticizer of the first polymer layer comprises a diester having four or more ethylene glycol repeating units, or wherein the plasticizer of the first polymer layer comprises molecules with an oxygen-to-carbon ratio of at least 0.32, or wherein the plasticizer of the first polymer layer comprises an ethylene glycol diester, and wherein the ethylene glycol diester has a weight-average molecular weight of at least 420 Daltons, or wherein the plasticizer of the first polymer layer has a composition derived from the dispersion solubility parameter δ. d Polar solubility parameter δ p and hydrogen bond solubility parameter δ h The total solubility parameter δ, which is composed of the contributions of the total solubility parameter δ, tot The polar solubility parameter δ p and the hydrogen bond solubility parameter δ h The contribution relative to the total solubility parameter δ tot The ratio is at least 0.

365.

16. The method according to claim 13, wherein the resin comprises 50wt%-80wt% acetate, 5wt%-20wt% hydroxyl content and 10wt%-45wt% aldehyde content.

Citation Information

Patent Citations

  • Control of adhesion of polyvinyl butyral sheet to glass

    US5728472A

  • Cellulose ester multilayer interlayers

    CN109195792A

  • Asymmetric laminates comprising asymmetric multiple layer interlayer

    US20180104932A1